2015
DOI: 10.1210/en.2014-1656
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inhibits Cavin-1 and Cavin-2 Expression and Down-Regulates Caveolae in Adipocytes

Abstract: During obesity, a hypoxic state develops within the adipose tissue, resulting in insulin resistance. To understand the underlying mechanism, we analyzed the involvement of caveolae because they play a crucial role in the activation of insulin receptors. In the present study, we demonstrate that in 3T3-L1 adipocytes, hypoxia induces the disappearance of caveolae and inhibits the expression of Cavin-1 and Cavin-2, two proteins necessary for the formation of caveolae. In mice, hypoxia induced by the ligature of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 76 publications
2
22
0
Order By: Relevance
“…Comparing with cavin-1 and cavin-2, cavin-3's function was not well established and cavin-4 was related to caveolin-associated muscle disease [16,20]. In 2015, Regazzetti et al [21] found that cavin-1 and cavin-2 were necessary for the formation of caveolae. Therefore, researchers supposed that cavin-1 and cavin-2 may be related to tumorigenesis, one of the functions of caveolae.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with cavin-1 and cavin-2, cavin-3's function was not well established and cavin-4 was related to caveolin-associated muscle disease [16,20]. In 2015, Regazzetti et al [21] found that cavin-1 and cavin-2 were necessary for the formation of caveolae. Therefore, researchers supposed that cavin-1 and cavin-2 may be related to tumorigenesis, one of the functions of caveolae.…”
Section: Introductionmentioning
confidence: 99%
“…Data indicate a correlation between the levels of cavin-1 (polymerase transcript release factor, PTRF) and caveolin-1 and the abundance of caveolae. Notably, cavin-1 can be recruited by caveolins to plasma membrane caveolar domains and is necessary for caveolae formation (43,44). In the present study, by determining the expression of these essential proteins involved in LDL transcytosis, including LDLR, caveolin-1, cavin-1 and clathrin, we observed that Ang II significantly upregulated the levels of LDLR, caveolin-1 and cavin-1, but Ang II exhibited no obvious effects on clathrin expression.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic effects may also be expected upon modulation of Cavin-2 expression. Indeed, hypoxia was recently shown to inhibit Cavin-2 expression in adipocytes and to alter caveolar formation (37). This led to the inhibition of insulin signaling and the establishment of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%